Imperative Role of Digital Twin in the Management of Hospitality Services - Ramnarayan; Rajesh Singh; Anita Gehlot; Kapil Joshi; Ashraf Osman Ibrahim Elsayed; Anas W. Abulfaraj; Faisal Binzagr; Salil Bharany (Science and Information Organization, 2023)
Digital twin implementation enables more effective terms of evaluation and planning, and also effective utilization of resources with a flood of knowledge to improve the real-time services. The hospitality industry settings utilize digital twin technologies to introduce new ideas with sensor, actuators, AR/VR improve production, and improve customer services. Currently, the hospitality industry is focused to create a fast, virtual world space where customers can get a real world of hospitality. The technologically digital twin of a vast inn office can be implemented to create both discrete and continuous event recreations in order to precisely conceptualize the events that occur in distinct frameworks. Based on the above facts, the adoption of the digital twin in the hospitality industry has gained significant attention. With this motivation, the study aims to investigate the significance and application of the digital twins in the hospitality industry for establishing innovative and digital infrastructure. In addition to this, the study discusses different elements that are significant for the digital twin. Finally, the article summarizes and recommends vital recommendation in the adoption of digital twin in hospitality industry.